Transmisi Nilai Kehidupan dengan Memahami Simbol, Makna, dan Pandangan Hidup dalam Tradisi Manoe Pucok di Aceh Selatan - Arfah Ibrahim (Jurnal Adabiya, 2019)
this research is aimed to explain the symbols and tools that are used in a ritual of Mano Pucok in South Aceh District. And also exploring the relation between society and ancient wisdom of their ancestor. Mano pucok traditionmainly held on wedding ceremonial and circumsition tradition, this research using qualitative method of analytical descriptive to explore the social phenomena by conducting etnograpy approachment. The result is confirmed that mano pucok is more that just a normal showering but as an institutional of religious values and ancient wisdom.Keywords: mano pucok, tradition, wedding, circumsition.